Web-Based Geographic Information System of Livable House in Kandolo Village - Rahmawati; Husmul Beze; Muslimin B (Politeknik Pertanian Negeri Samarinda, 2022)
A livable house is abbreviated as the feasibility of a residential house which can be measured from 2 aspects, namely the physical quality of the house and the quality of house facilities. The physical quality of the residential house is measured by 3 variables, namely the type of roof, the type of wall, and the type of floor, while the quality of the housing facilities is measured by 2 variables, namely the source of lighting and the availability of toilet facilities. In this study, the authors use the prototype method using data analysis and system design. This web-based geographic information system for livable houses in Kandolo Village aims to assist in the data collection process for livable houses in Kandolo Village. The results of this study 257 house data have been entered, of which 247 houses are suitable for livable on, 6 houses that are less suitable for livable on, and 4 houses that are not suitable for livable on. For visitors, this system functions to select houses that are livable by looking at several registered pins, then the system will take the resident data detail page. Then in the detail section of citizen data, there will be some resident data, photos of houses, and routes to their destination. From the application trial results, the author conducted a black box test with 11 test class items and respondent tests for direct users at the Kandolo Village Office where the features are used to well and are accepted among the community.